인지 장애 진단ㆍ평가ㆍ분석을 위한 생체신호 장비 개발에 대한 수요조사: 한방신경정신과학회 회원들을 대상으로 - 최유진; Yujin Choi Ji; 김지혜; Hye Kim; 김가혜; Kahye Kim; 김재욱; Jaeuk Kim (동의신경정신과학회지, 2020)
Objectives: The purpose of this study was to identify the needs of bio-signal devices for the diagnosis, assessment, and analysis of neurocognitive disorder in Korean medicine (KM) hospitals and clinics. Methods: A questionnaire was developed to survey the current status of medical device use, and diagnosis and interventions for patients with cognitive disorders in KM hospitals and clinics. November 11∼December 2, 2019, 114 responses (71.9% completed) were collected by internet-based questionnaires from the members of the Korean society of Oriental Neuropsychiatry. Results: The clinical requests were in the descending order of hematology analyzer, ultrasound imaging system, and electroencephalography among the 15 most commonly used devices of which research would support for their clinical usability. The biosignal-based devices showed the highest research demands for patients with mild cognitive impairment rather than more severe stages of cognitive impairment. Prevention rather than diagnosis, or several treatment regimens was the strongest clinical area of the KM for patients with neurodegenerative cognitive impairment. Many responded that five to 10 minutes of test duration and 20,000 won to 30,000 won of cost would be appropriated for a new device to be developed. Conclusions: There were strong demands for the development of bio-signal devices for neurocognitive disorders among the KM doctors. Specifically, it showed high needs for the technology that can be used in the prevention area of cognitive disorders. Additionally, new medical devices to assess cognitive functions and to obtain KM pattern-related information were the high needs.